2014
DOI: 10.1007/s11162-014-9352-9
|View full text |Cite
|
Sign up to set email alerts
|

Using Multiple Measures to Make Math Placement Decisions: Implications for Access and Success in Community Colleges

Abstract: Community college students are often placed in developmental math courses based on the results of a single placement test. However, concerns about accurate placement have recently led states and colleges across the country to consider using other measures to inform placement decisions. While the relationships between college outcomes and such measures as high school GPA, prior math achievement, and noncognitive measures are well-known, there is little research that examines whether using these measures for cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
54
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(57 citation statements)
references
References 26 publications
(40 reference statements)
3
54
0
Order By: Relevance
“…Further, our results demonstrate that some magnitude of students who would have been previously required to take developmental education based solely on their PERT score were successful in passing gateway math. This finding offers support to numerous other studies that have shown the benefit of using multiple measures (e.g., Ngo & Kwon, 2015; Scott-Clayton, Crosta, & Belfield, 2014). A combination of flexible cutoff scores (or bands) with multiple measures such as high school transcript information (course taking and grades) might be the best approach to developmental education placement.…”
Section: Discussionsupporting
confidence: 86%
“…Further, our results demonstrate that some magnitude of students who would have been previously required to take developmental education based solely on their PERT score were successful in passing gateway math. This finding offers support to numerous other studies that have shown the benefit of using multiple measures (e.g., Ngo & Kwon, 2015; Scott-Clayton, Crosta, & Belfield, 2014). A combination of flexible cutoff scores (or bands) with multiple measures such as high school transcript information (course taking and grades) might be the best approach to developmental education placement.…”
Section: Discussionsupporting
confidence: 86%
“…Another study focused on a placement test versus student's high school information and concluded that testing at the university in the first year is more useful [3]. A third study using data from the Los Angeles Community College district indicated that multiple variables are useful when conducting the placement process, such as high school GPA combined with prior math background [20].…”
Section: Research Questionsmentioning
confidence: 99%
“…Reisel says "the use of math ACT scores as a predictor of success in the program is reasonable, but should be used with caution" while studies by Hoffman and Lowitzki, Munro, and Zheng et al argue that high school GPA is more predictive than standardized test scores [14,31,32]. Foley-Peres and Poirier found that SAT scores were less important than placement test scores, and Ngo and Kwan indicated that multiple variables should be included when placing students in the initial math class [19,20]. Given this literature, it is reasonable to expect that ACT Math score will be a significant variable in the model as well as other variables such as high school GPA.…”
Section: Expected Outcomesmentioning
confidence: 99%
“…Higher education scholars have documented how variables such as high school GPA and prior course-taking are often stronger predictors of college success than test scores (Adelman, 2006;Armstrong, 2000;DesJardins & Lindsey, 2007). Challenging the over-reliance on placement testing, researchers have also found that supplementing or even replacing placement tests with high school transcript (HST) information may improve course placement (Ngo & Kwon, 2015;Scott-Clayton, Crosta, & Belfield, 2014). Further, math diagnostics can also be a potentially valuable resource for math faculty and student support center personnel.…”
Section: Using High School Transcript Data and Diagnostic Informationmentioning
confidence: 99%
“…This stems from a long line of research that has shown that high school grades and course taking are strong predictors of postsecondary success (e.g., Adelman, 2006;Armstrong, 2000;DesJardins & Lindsay, 2007). Indeed, using such measures as HSGPA and prior math course taking during assessment and placement can increase student access to higher-level courses without compromising success in those courses, particularly for African-American and Latina/o students (Ngo & Kwon, 2015).…”
Section: Introductionmentioning
confidence: 99%